Locally dividing macrophages in normal and inflamed mammary glands. - Jutila, M A (1986)
Goat mammary macrophage division in vivo was assessed by detection of mitotic figures, by autoradiographic measurement of the uptake of 3H thymidine, and by a 96-well proliferation assay. Autoradiography revealed that 3.74 +/- 0.77% of nonstimulated mammary macrophages were actively synthesizing DNA. Eight days of sterile inflammation, induced by lipopolysaccharide or thioglycollate, increased mammary macrophage division (10.9 +/- 2.1%). The division increased within 2 h after inducing inflammation with thioglycollate. After 1 day, the rate of division decreased, and another increase occurred 3-4 days later. The high rate of division was maintained for greater than 60 days after the induction of sterile inflammation. Division was further shown to occur by injecting 3H-thymidine directly into the mammary gland, harvesting the macrophages 1.5 h later, and determining incorporation by autoradiography. The results of all assays of division were in agreement, suggesting they reflected the same event. The dividing cells were nonspecific esterase-positive, adherent, motile, phagocytic, and had morphological characteristics of macrophages.